An independent assessment of reliability of the Melbourne Cerebral Palsy Hip Classification System. (October 2017) - Shrader, M. W.; Koenig, A. L.; Falk, M.; Belthur, M.; Boan, C.
Purpose: Neuromuscular (NM) hip dysplasia is common in patients with cerebral palsy (CP). Traditionally, migration percentage (MP) has been used to measure the severity of NM hip dysplasia; however, the MP has some limitations. The purpose of this study is to determine the intra- and inter-reliability of the Melbourne Cerebral Palsy Hip Classification System in the typical paediatric population of patients with CP. Methods: A total of 65 anteroposterior pelvis radiographs in patients (age range 12 years to 21 years) with CP spanning all grades (I to VI) of the classification system were identified and collected for analysis in this institutional review board approved study. Four paediatric orthopaedic surgeons and one orthopaedic surgical resident classified each radiograph according to the Melbourne system. Then, at least four weeks later, the raters repeated the process with a re-randomised order of radiographs. Statistical analysis was performed using the intraclass correlation coefficient (ICC) where < 0 denotes poor agreement and > 0.8 indicates almost perfect agreement. Results: The interobserver reliability was found to be excellent with the ICC of 0.853 (0.813 to 0.887) and 0.839 (0.795 to 0.877). The intraobserver reliability was also found to be excellent with the ICC in the range of 0.838 to 0.933 among the raters. Subgroup analysis indicated no differences in the reliability of observers based on clinical experience. Conclusion: This study independently demonstrates that the Melbourne Cerebral Palsy Hip Classification System for NM hip dysplasia in patients with CP can be reliably used for communication among various healthcare providers and research and epidemiological purposes.